Influence of Green Marketing, Product Hygiene, and Brand Identity on Repurchase Intention Starbucks in Semarang City - Halidazia Nuril Ahfa; Fatchun - Hasyim; Andi - Setiawan (Admisi dan Bisnis, 2022)
Starbucks Coffee is the largest coffee shop company in the world which is engaged in the food and beverage industry. This study aims to analyze the influence of Green Marketing, Product Hygiene, and Brand Identity on Repurchase Intention of Starbucks In Semarang City. Data collection methods used are questionnaires and literature review. The questionnaire used was the Agree-Disagree Scale with a scoring of 10 points (1-10) The sample collection method used is purposive sampling with 100 people of Starbucks consumers in Semarang. The analysis technique used in this research are vailidity test, reliability test, normality test, heteroscedastisity test, multicollinearity test, linearity test, multiple linear regression, t test, F test and coefficient of determination. The data in this study are analyzed with SPSS 25. Based on the results, Green Marketing (X1), Hygiene Product (X2), and Brand Identity (X3)  have a significant positive effect of Repurchase Intention Starbucks In Semarang City. This research is expected to be a solution to the problems that occurred during the COVID-19 pandemic by applying green marketing, product hygiene, and brand identity to improve Repurchase Intention so that Starbucks will get higher number consumers repurchase intention